The National Parliamentary Arena and Methods of Open Coordination: Explaining the Frequency of OMC-related Executive-legislature Interactions - Rik de Ruiter (Journal of Contemporary European Research, 2011)
This article tests the importance of different factors for the frequency with which information from open methods of coordination (OMCs) is used in parliamentary debates. Previous research has shown that OMCs provide the executive and the legislature with information on best and worst national policy practices, enabling them to adopt different strategies. First, a national government can fame its own policies with the use of information from OMCs. Second, information from OMCs can be used by parliamentarians of opposition parties to shame the policies of the incumbent government. A study of Dutch parliamentary debates indicates that the Dutch government uses more information from OMCs to fame its own policies when OMCs have a developed infrastructure and/or a treaty base. Parliamentarians from opposition parties use more information from OMCs adopted for policy areas in which there was already EU-level activity prior to the OMC, and the government provided information on the substance of OMCs to members of national parliaments.